Constitutive model for describing flow behaviour of Fe–18Cr–10Mn–0·39N austenitic stainless steel. (March 2014) - Behjati, P.; Araghchi, M.; Kermanpur, A.; Najafizadeh, A.
<x content-type="archive" xml:space="preserve">Abstract</x> In the present work, a constitutive model is developed to describe the flow behaviour of metastable Fe–18Cr–10Mn–0·39N (wt-%) austenitic stainless steel, considering deformed microstructure of the alloy as a composite material (mixture of austenite/α′-martensite). The results of previous studies are used to validate the model. It is shown that the developed model is more appropriate to predict flow behaviour of the metastable alloy undergoing considerable martensitic transformation during deformation when compared with the modified Ludwik equation suggested in some earlier works.